Theorizing crisis communication - Sellnow, Timothy L. (Timothy Lester) 1960-; Seeger, Matthew W. (Matthew Wayne) 1957- (Hoboken, NJ John Wiley & Sons, 2021)
We were gratified and somewhat surprised at the success of the first edition of Theorizing Crisis Communication. Although we believed a summary of crisis theory was important, we also assumed that crisis communication remained a relatively specialized area of communication research. The success of the first edition demonstrated that crisis communication is recognized as a critical area of practice for individuals, organizations, communities, and society at large and is becoming increasingly mainstream. The second edition of Theorizing Crisis Communication reviews a larger body of theory reflective of the continuous growth in crisis communication scholarship. In addition to the discussion of more theories in all chapters, this edition includes new chapters on theory formation, social media, and applications of theory, as well as expanded treatment of technology, resilience, and risk, among others."--
Includes bibliographical references (311-344) and index (345-353)
Keywords: Content analysis (Communication); Crisis management; Emergency management; Communication -- Research